Inferring task performance and confidence from displays of eye movements. Issue 6 (23rd August 2020) - Emhardt, Selina N.; van Wermeskerken, Margot; Scheiter, Katharina; van Gog, Tamara
Summary: Eye movements reveal what is at the center of people's attention, which is assumed to coincide with what they are thinking about. Eye‐movement displays (visualizations of a person's fixations superimposed onto the stimulus, for example, as dots or circles) might provide useful information for diagnosing that person's performance. However, making inferences about a person's task performance based on eye‐movement displays requires substantial interpretation. Using graph‐comprehension tasks, we investigated to what extent observers ( N = 46) could make accurate inferences about a performer's multiple‐choice task performance (i.e., chosen answer), confidence, and competence from displays of that person's eye movements. Observers' accuracy when judging which answer the performer chose was above chance level and was higher for displays reflecting confident performance. Observers were also able to infer performers' confidence from the eye‐movement displays; moreover, their own task performance and perceived similarity with the performer affected their judgments of the other's competence.